Unresponsiveness of colon cancer to BRAF(V600E) inhibition through feedback activation of EGFR - Prahallad, Anirudh; Sun, Chong; Huang, Sidong; Di Nicolantonio, Federica; Salazar, Ramon; Zecchin, Davide; Beijersbergen, Roderick L.; Bardelli, Alberto; Bernards, René (Nature (London), 2012)
Inhibition of activated BRAF has been ineffective in colon cancers with the mutation; here, this is shown to be due to the feedback activation of the epidermal growth factor receptor (EGFR) in response to BRAF inhibition. Inhibition of the BRAF(V600E) oncoprotein by the small-molecule drug PLX4032 (vemurafenib) is highly effective in the treatment of melanoma 1 . However, colon cancer patients harbouring the same BRAF ( V600E ) oncogenic lesion have poor prognosis and show only a very limited response to this drug 2 , 3 , 4 . To investigate the cause of the limited therapeutic effect of PLX4032 in BRAF ( V600E ) mutant colon tumours, here we performed an RNA-interference-based genetic screen in human cells to search for kinases whose knockdown synergizes with BRAF(V600E) inhibition. We report that blockade of the epidermal growth factor receptor (EGFR) shows strong synergy with BRAF(V600E) inhibition. We find in multiple BRAF ( V600E ) mutant colon cancers that inhibition of EGFR by the antibody drug cetuximab or the small-molecule drugs gefitinib or erlotinib is strongly synergistic with BRAF(V600E) inhibition, both in vitro and in vivo . Mechanistically, we find that BRAF(V600E) inhibition causes a rapid feedback activation of EGFR, which supports continued proliferation in the presence of BRAF(V600E) inhibition. Melanoma cells express low levels of EGFR and are therefore not subject to this feedback activation. Consistent with this, we find that ectopic expression of EGFR in melanoma cells is sufficient to cause resistance to PLX4032. Our data suggest that BRAF ( V600E ) mutant colon cancers (approximately 8–10% of all colon cancers 2 , 3 , 5 ), for which there are currently no targeted treatment options available, might benefit from combination therapy consisting of BRAF and EGFR inhibitors.